MODEL OPTIMASI KUJUNGAN WISATA RELIGI DI KARESIDENAN SEMARANG DENGAN METODE SINGLE LINKAGE (Information Technology and Telematics, 2016)
Abstract—Tourism has long been a concern, both in terms of economics, politics, state administration, and sociology, tourism is a wide range of tourist activities and supported a wide range of facilities and services provided by the public, employers, government and local governments. Religious Tourism is one type of tourism is closely related to religion or religious embraced by humans. Application religion tourism with Single Linkage method which utilizes WebGIS was created to assist travelers in visiting time optimization based unit of distance is calculated using the formula Euclidean Distance and make it easier to find information about the existing Religious Tourism diKaresidenan Semarang.Dengan provide a variety of features to be utilized by user or user to know the various info and tourist locations where the point is derived and the search for a couple of tours based on the distance and the predetermined path from point pusat.Agar these applications can continue to grow user or users can participate in providing input in the form of suggestion that this application is growing. Keywords : Religion tourism, Single Linkage, Optimzation, WebGIS